Keratinocyte PIEZO1 modulates cutaneous mechanosensation - Alexander R Mikesell; Olena Isaeva; Francie Moehring; Katelyn E Sadler; Anthony D Menzel; Cheryl L Stucky (eLife, 2022)
Epidermal keratinocytes mediate touch sensation by detecting and encoding tactile information to sensory neurons. However, the specific mechanotransducers that enable keratinocytes to respond to mechanical stimulation are unknown. Here, we found that the mechanically-gated ion channel PIEZO1 is a key keratinocyte mechanotransducer. Keratinocyte expression of PIEZO1 is critical for normal sensory afferent firing and behavioral responses to mechanical stimuli in mice.